Chatbot Prototype Training Using Deep Learning Methods For Tourism in North Sumatra - Fibriasari, Hesti; Putri, Tansa Trisna Astono; Widiastuti, Uyuni (Universitas Negeri Medan, 2023)
One of the several foreign exchange industries with considerable expansion potential is tourism. One is the province of North Sumatra, which has numerous intriguing tourist attractions. Advertising and inadequate tourism information management systems are factors that are impeding the growth of the tourism industry. The younger generation still has very little understanding of artificial intelligence and its applications for Chatbots and support services. A program called a Chatbot makes to hold chats for you. As a result, instruction requires in the design and use of deep-learning Chatbots. By offering guidance, examples, and hands-on training on tourist Chatbot prototypes from North Sumatra, this non-profit endeavor attempted to address the issue at hand. The PKM program's activities include: 1) instruction in marketing strategies including tourist information management systems. 2) instruction in the fundamental ideas of artificial intelligence, particularly Chatbots. 3) instruction in deep learning for Chatbot construction; 4) instruction in utilizing the Chatbot application. It envisaged that the outcomes of this activity would promote public awareness usage of Chatbot applications to discover data regarding tourist attractions around the province of North Sumatra as awareness among tourists.